2024
DOI: 10.3390/cancers16061207
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Radical Prostatectomy by the Hugo Robotic-Assisted Surgery (RAS) System and the da Vinci System: A Comparison between the Two Platforms

Hsien-Che Ou,
Lucian Marian,
Ching-Chia Li
et al.

Abstract: Objective: In a previous study, we proved that an experienced urologist is more likely to adapt to the Hugo RAS system. Based on this, we further examine various parameters in this study. Parameters included in this study consisted of console time, functional outcomes, and oncological outcomes. Materials and Methods: A total of 60 patients who underwent robot-assisted radical prostatectomy (RARP) performed by a single surgeon using the da Vinci (DV) system (n = 30) or the Hugo RAS system (n = 30) between March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…We assessed 37 documents, and 12 papers met our inclusion criteria, including 579 patients. Four studies were conference abstracts [18][19][20][21], and eight were reported in full-text [3,[22][23][24][25][26][27][28]. Five citations [29][30][31][32][33] were duplicated studies by the same group of authors and were retained exclusively because they provided additional data compared to the most recent included report [22,23,26,28].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…We assessed 37 documents, and 12 papers met our inclusion criteria, including 579 patients. Four studies were conference abstracts [18][19][20][21], and eight were reported in full-text [3,[22][23][24][25][26][27][28]. Five citations [29][30][31][32][33] were duplicated studies by the same group of authors and were retained exclusively because they provided additional data compared to the most recent included report [22,23,26,28].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Four studies were conference abstracts [18][19][20][21], and eight were reported in full-text [3,[22][23][24][25][26][27][28]. Five citations [29][30][31][32][33] were duplicated studies by the same group of authors and were retained exclusively because they provided additional data compared to the most recent included report [22,23,26,28]. Specifically, Bravi et al [29] provide additional data on postoperative PSA and console time, while Totaro et al [30], Ragavan et al [31], Ou et al [32], and Veccia/Antonelli et al [33] provide additional information on docking parameters.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations